Ice Forces and Ship Response to Ice. Consolidated Report - Daley, C.; St John, J. W.; Brown, R.; Glen, I. (1990)
Conclusions from this study include: (1) Both peak force and peak pressures during an impact increase with ice severity (ice thickness and ice strength). (2) In arctic regions, operation at higher latitudes increases ice severity and therefore ice loads. (3) Peak pressure during an impact appears to be only weakly dependent on impact speed, and no dependency was discernable from the measured data. (4) Peak force during an impact does increase with impact speed and a linear relationship between them appears reasonable. (5) Total force increases with increasing contact area but average pressure decreases with increasing contact area. (6) The average pressure distribution on the ship hull within the impact zone at an instant in time is asymptotic to a line of constant force at large areas and to a line proportional to a negative fractional power of area (in the range of -0.2 to -0.3) at small areas, The latter asymptote appears related to the triaxial crushing strength versus strain rate dependency of the ice. (7) Extreme value distributions of ice force and pressure for the most severe ice conditions show Frechet type or upward curving distributions. Intermediate ice conditions follow a Gumbel or linear type distribution. Only the distributions for data recorded in light first-year ice conditions appear to be bounded or Weibul type distributions.